2013
DOI: 10.1194/jlr.p035238
|View full text |Cite
|
Sign up to set email alerts
|

Novel gene-by-environment interactions: APOB and NPC1L1 variants affect the relationship between dietary and total plasma cholesterol

Abstract: This article is available online at http://www.jlr.org Supplementary key words dietary cholesterol • total cholesterol • cardiovascular disease • Niemann-Pick C1-like 1 Cardiovascular disease (CVD), including coronary heart disease and carotid artery disease (CAAD), is the leading cause of death in developed countries, accounting for approximately one-third of all deaths in adults over age 35 ( 1 ). One of the key risk factors for CVD is hypercholesterolemia ( 2 ), with epidemiologic studies demonstrating a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Further work is needed to elaborate the role that PCIF1 plays in PLTPa. on lipid levels ( 47,59 ), leading to a more conservative estimate of the effect of PLTPa on CAAD status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further work is needed to elaborate the role that PCIF1 plays in PLTPa. on lipid levels ( 47,59 ), leading to a more conservative estimate of the effect of PLTPa on CAAD status.…”
Section: Discussionmentioning
confidence: 99%
“…The study population is a subset (n = 1,115) of the previously described CLEAR study ( 8,(10)(11)(12)(40)(41)(42)(43)(44)(45)(46)(47) PLTP region SNP associations with PLTPa. SNPs with у 1% frequency identifi ed in the PLTP region between 50 kb upstream of the fi rst codon or downstream of the last (n = 124 SNPs) were included in our analyses of the genetic predictors of PLTPa.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…One of these hypotheses is that geneby-environment interactions among common SNVs comprise a large portion of heritability ( 18,19 ). Given the wide variety of pharmacologic and dietary determinants on PON1 expression and enzyme activity ( 20 ), the potential interaction of these environmental factors with PON1 variants could represent another important source of trait heritability.…”
Section: Discussionmentioning
confidence: 99%
“…The rs2072183 polymorphism is the top SNP within the NPC1L1 gene most significantly associated with an increased plasma LDL-C level according to a genomewide analysis of Caucasians. However, this polymorphism appears to be associated with reduced LDL-C levels in East Asians 17) , and other recent studies have demonstrated that the rs2072183 polymorphism is associated with increased cholesterol levels in men only and may interact with dietary cholesterol to determine the cholesterol levels 18,19) . It is also possible that mutations in NPC1L1 or polymorphisms in some other genes influencing cholesterol absorption or other pathways inherited from the mother, who also had a low LDL-C level (1.7 mmol/L), may have contributed to the reduced plasma sitosterol, campesterol and LDL-C levels in the affected sibling relative to the proband.…”
Section: Molecular Geneticsmentioning
confidence: 99%